A splitting algorithm for dual monotone inclusions involving cocoercive operators - Vu, Bang Cong (Advances in computational mathematics, 2013)
We consider the problem of solving dual monotone inclusions involving sums of composite parallel-sum type operators. A feature of this work is to exploit explicitly the properties of the cocoercive operators appearing in the model. Several splitting algorithms recently proposed in the literature are recovered as special cases.